Penggunaan Adsorben Bentonit pada Proses Pencucian Kering dalam Pemurnian Biodiesel Minyak Jelantah - Amaliah Azis, Hijrah; Mustam, Mariaulfa; Ramdani, Nurfika; Amin, Ida Ifdaliah; Sari, Nurmala; Gregorius, Geraldy (Jurnal Teknik Kimia USU, 2023)
Biodiesel can be made by utilizing used cooking oil through a chemical process, namely through a transesterification reaction, namely changing the oil (triglycerides) into fatty acid methyl esters. Washing must be done to remove the remaining impurities in biodiesel. The dry washing method is purification by utilizing the adsorption process to remove impurities in crude biodiesel. Bentonite is an alternative adsorbent that can be used as dry washing in the biodiesel refining process because it is cheaper, abundant in nature and has a layered structure with the ability to swell. The purpose of the study was to determine the ability of bentonite activated with acid as a dry washing agent in biodiesel purification. The research method used is the dry washing process method using bentonite adsorbents. The application of bentonite adsorbent as much as 6 grams with a contact time of 3 hours is the best operating condition to produce biodiesel with a pH of 6 and a clarity value of 96.7.